2017
DOI: 10.1038/ng.3837
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variants that alter protein code often disrupt splicing

Abstract: The lack of tools to identify causative variants from sequencing data greatly limits the promise of precision medicine. Previous studies suggest that one-third of disease-associated alleles alter splicing. We discovered that the alleles causing splicing defects cluster in disease-associated genes (for example, haploinsufficient genes). We analyzed 4,964 published disease-causing exonic mutations using a massively parallel splicing assay (MaPSy), which showed an 81% concordance rate with splicing in patient tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
236
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(248 citation statements)
references
References 45 publications
11
236
1
Order By: Relevance
“…We recently developed Massively Parallel Splicing Assay (MaPSy), which enables us to directly compare the splicing performance of thousands of mutant and wildtype substrates [40, 41]. Thermodynamically less stable RNAs (higher free-energy structures) splice more efficiently, particularly those with more open (unpaired) bases in the splice-site regions (Figure 5A,B).…”
Section: Disease Mutations That Alter Rna Secondary Structuresmentioning
confidence: 99%
“…We recently developed Massively Parallel Splicing Assay (MaPSy), which enables us to directly compare the splicing performance of thousands of mutant and wildtype substrates [40, 41]. Thermodynamically less stable RNAs (higher free-energy structures) splice more efficiently, particularly those with more open (unpaired) bases in the splice-site regions (Figure 5A,B).…”
Section: Disease Mutations That Alter Rna Secondary Structuresmentioning
confidence: 99%
“…However, the predictive power of these models may come almost entirely from sequence conservation rather than the mechanistic understanding of splicing 18,19 . These models predict that human genetic variation, and especially rare variation, often disrupt sequence features required for proper exon recognition, but it is difficult to verify the accuracy of these predictions at large scales Several groups have developed massively parallel reporter assays of splicing 8,14,20,21 . Most of these assays look at a small set of exons and mutate them to understand which elements are important for splicing.…”
Section: Main Textmentioning
confidence: 99%
“…Importantly, these methods have allowed us to better quantify how individual ESEs and ESSs combine to contribute to exon recognition in a small number of exon contexts, and can be used to build more general predictive models for exon splicing. Recently, a survey of disease variants within a much broader set of human exons found that~10% of these variants had exon recognition defects 20 . Despite the recent progress, there are still several limitations inherent to these large-scale approaches.…”
Section: Main Textmentioning
confidence: 99%
“…It has been estimated that ~4% of synonymous mutations are deleterious, since they result in aberrant splicing due to disruption of exonic splicing enhancers (25). Another study showed that ~10% of exonic disease-associated alleles disrupt splicing (26). Furthermore, it was proposed that ~22% of disease alleles that were originally classified as missense mutation may in fact affect splicing (27).…”
Section: Introductionmentioning
confidence: 99%